2016
DOI: 10.5007/2175-8026.2016v69n3p173
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the future: teaching reading and writing at the Universidad Nacional de Entre Rios

Abstract: Since the 1990s, in Argentina there has been considerable concern over whether higher education institutions must undertake the responsibility of teaching academic skills to their student population or if both undergraduates and graduates ought to cope with the enculturation process without assistance. Although academics seem to have reached an agreement and have put forward a number of actions aimed at facilitating the access of university students into their target discourse communities, there is still heate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…Undergraduate students report numerous advantages of receiving critical pedagogy at university. However, there is a controversy among university teachers about the inclusion of academic literacy in higher education (Waigandt et al, 2016). Through in-depth interviews Colombo, Prior, Colombo, and Prior (2016) found that a group of teachers is aware of the importance of academic literacy and has a positive attitude to their teaching while the other group argues that students of these education level must already perform critical reading and writing skills.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Undergraduate students report numerous advantages of receiving critical pedagogy at university. However, there is a controversy among university teachers about the inclusion of academic literacy in higher education (Waigandt et al, 2016). Through in-depth interviews Colombo, Prior, Colombo, and Prior (2016) found that a group of teachers is aware of the importance of academic literacy and has a positive attitude to their teaching while the other group argues that students of these education level must already perform critical reading and writing skills.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A nivel de Latinoamérica, Argentina fue uno de los países iniciadores en investigaciones sobre prácticas de la lectura y la escritura en la educación universitaria, estas en su mayoría fueron estudios diagnósticos, que tendían a identificar las dificultades que presentaban los estudiantes en la lectura y escritura, lo que conllevó a la creación de talleres y cursos de lenguaje para estudiantes de primer semestre, pero desligados de las asignaturas e insuficientes, dado que al ingresar los estudiantes se enfrentaban a nuevas formas discursivas, en las cuales se les pedía leer y escribir de una forma diferente y con diferente bibliografía (Carlino, 2013). Por tanto, Carlino (2018); Cartolari et al, (2013) ;Marinkovich, et al, (2016) y Waigandt, et al, (2016) realizan estudios sobre la enseñanza de la lectura y escritura como prácticas propias de sus disciplinas en la formación universitaria. De esta manera, se han ido creando programas de alfabetización académica a lo largo del plan de estudios en las carreras universitarias como política institucional (Moyano, 2018;Moyano y Giudice, 2016).…”
Section: Introductionunclassified